P2Y1 gene deficiency protects from renal disease progression and capillary rarefaction during passive crescentic glomerulonephritis - Hohenstein, Bernd; Renk, Sindy; Lang, Kathrin; Daniel, Christoph; Freund, Monique; Léon, Catherine; Amann, Kerstin Ute; Gachet, Christian; Hugo, Christian (Journal of the American Society of Nephrology, 2007)
The metabotropic receptor P2Y1 is necessary for full ADP-induced platelet activation and is localized on various intrinsic renal cells, including mesangial cells, podocytes, and endothelial cells. To date, nothing is known about the role of the P2Y1 receptor during inflammatory renal disease. The role of the P2Y1 receptor was investigated using 22 P2Y1 gene-deficient (-/-) and 27 wild-type (wt) mice during the time course of passive crescentic nephrotoxic glomerulonephritis. Six P2Y1 -/- and six wt mice served as undiseased controls. Renal tissues were harvested on days 1, 10, and 28 after disease induction. No renal phenotype was found in P2Y1 -/- versus wt mice. In contrast, during crescentic glomerulonephritis, approximately 50% of all wt mice died, whereas all P2Y1 -/- mice survived. Renal function as assessed by creatinine clearance measurements, glomerulosclerosis, and tubulointerstitial injury indices as well as glomerular and interstitial matrix expansion were improved significantly in P2Y1 -/- compared with wt mice. These changes were preceded by reduced glomerular and peritubular capillary rarefaction indices in P2Y1 -/- compared with wt mice. The alteration of the rates of both peritubular apoptosis and endothelial cell proliferation suggests improved capillary preservation in P2Y1 -/- mice early in disease (day 10) and an additional enhanced repair reaction in P2Y1 -/- mice at the late time point (day 28), whereas injury on day 1 seemed to be equivalent in both groups. It is concluded that loss of P2Y1 receptor function safeguards against capillary loss, fibrosis, and death by renal failure during experimental crescentic glomerulonephritis. Copyright © 2007 by the American Society of Nephrology.
Created from Fastlane, Scopus look-up